Long Intergenic Noncoding RNA 00641 Promotes Growth and Invasion of Colorectal Cancer through Regulating miR-450b-5p/GOLPH3 Axis. (15th June 2022) - Hong, Zhongshi; Pan, Jianpeng; Chen, Mingliang; Deng, Xian; Chen, Zhichuan; Wang, Chunxiao; Qiu, Chengzhi
Abstract : Background . Long noncoding RNAs (lncRNAs) have a vital function in tumor onset and progress. For instance, long intergenic noncoding RNA 00641 (LINC00641) has been linked to cancer modulation. Nonetheless, the precise biological roles of LINC00641 in colorectal cancer (CRC) remain elusive. Methods . The expression levels of LINC00641 as well as the docking sites for LINC00641 and miR-450b-5p were analyzed using public data resources and web-based analytic tools. The putative downstream targets of miR-450b-5p were also predicted. Next, we evaluated the biological functions and the contents of LINC00641 in CRC both in vivo and in vitro . We next explored the influence of LINC00641 on the growth, migration, and infiltration of CRC cells via cell proliferation, migration, and invasion experiments. Besides, qRT-PCR, western blotting, flow cytometry, luciferase enzyme reporter assay, and in vivo tumorigenicity assays were conducted. Results . Our results confirmed that LINC00641 was markedly upmodulated in CRC tissues and CRC cell lines, and the upmodulation was linked to poor survival. Notably, the proliferative and migratory abilities of HCT-116 and SW480 cells were significantly inhibited by the knockdown of LINC00641 both in vitro and in vivo, illustrating that LINC00641 exerted a tumor-promotion role in CRC. Mechanistically, LINC00641 could competitively bind miR-450b-5p, thereby expunging its inhibitory effect on GOLPH3 expression. Moreover, miR-450-5p and GOLPH3 were able to reverse LINC00641-mediated cellular processes. Conclusions . Overall, the findings of this study suggest that LINC00641 promotes the proliferative and migratory abilities of CRC through sponging the miR-450b-5p/GOLPH3 axis.